Menstrual regulation: examining the incidence, methods, and sources of care of this understudied health practice in three settings using cross-sectional population-based surveys - Suzanne O. Bell; Mridula Shankar; Funmilola OlaOlorun; Elizabeth Omoluabi; Anoop Khanna; Danish Ahmad; Georges Guiella; Caroline Moreau (BMC Women's Health, 2023)
Plain English Summary Menstrual regulation, or bringing back a late period, is an understudied practice that women may use when they are worried they are pregnant but that may be viewed as distinct from abortion. This study seeks to measure the frequency of menstrual regulation in Nigeria, Cote d’Ivoire, and Rajasthan, India, overall and by women’s characteristics and to describe the methods and sources women use. We used data from representative surveys of women aged 15–49 years old in each study setting. We asked women whether they had ever done something to bring back a late period at a time when they were worried they were pregnant, and if so, what methods and sources they used. Results indicate that menstrual regulation may be a common practice, particularly in West Africa; the observed one-year rates were 22.6 menstrual regulations per 1,000 women aged 15–49 in Nigeria and 20.6 menstrual regulations per 1000 women in Cote d’Ivoire; women in Rajasthan only reported 3.3 menstrual regulations per 1000 women per year. Menstrual regulations primarily involved traditional or “other” methods in Nigeria (47.8%), Cote d’Ivoire (70.0%), and Rajasthan (37.6%) and traditional or “other” sources (49.4%, 77.2%, and 40.1%, respectively). These findings suggest menstrual regulation is not uncommon and may put women’s health at risk given the reported methods and sources used. Results have implications for abortion research and our understanding of how women manage their fertility.